The effect of age, severity, and mechanism of injury on risk of death from major trauma in Western Australia - Fatovich, D.; Jacobs, Ian; Langford, S.; Philipps, M. (Lippincott Williams & Wilkins, 2013)
Background: We examined the association between age, mechanism of injury, and Injury Severity Score (ISS) on mortality in major trauma. Methods: We used 9 years of population-based linked major trauma (ISS 915) registry data for Western Australia (N = 4,411). These were categorized using the Sampalis classification of injury severity: survivable (ISS 16Y24), probably survivable (ISS 25Y49), and nonsurvivable (ISS 50+). Age was categorized as younger than 15 years, 15 to 64 years, and 65 years or older. Multivariablelinear logistic regression analysis was used to examine the risk of death. Results: Motor vehicle crashes (MVCs) were most prominent for those younger than 65 years, and falls dominated the 65 years and older group. The median ISS for the three age groups were 20, 25, and 24, respectively (p = 0.001). The proportion of deaths in the three groups were 7.2%, 11.5%, and 30.1%, respectively (p = 0.0001). Falls were the most common cause of death. The inflexion point, above which the risk of death increases exponentially, was age 47 years. For the potentially survivable ISS 25 to 49 group, the inflexion point was age 25 years. After adjusting for age and ISS, falls had the greatest risk for death (odds ratio, 1.62; 95% confidence interval, 1.21Y2.18). A lower ISS had a disproportionate effect on the elderly. Conclusion: The risk for major trauma death increases as age increases, with the inflexion point at age 47 years. Those younger than 15 years have a significantly lower ISS. The elderly have an increased risk for death following falls.